Copper Extraction Using LIX 84 as a Mobile Carrier in the Emulsion Liquid Membrane Process (Journal of Applied Membrane Science & Technology, 2023)
Extensive research has been conducted to address the growing global demand for copper by exploring effective methods of extraction and recovery across various industries. The emulsion liquid membrane (ELM) has emerged as a viable option for efficiently extracting and recovering metals from waste solutions. Due to its advantageous features, the extraction and recovery of copper from a simulated copper solution was investigated. In the ELM, various parameters can affect the stability and efficiency of copper extraction which include agitation speed, treat ratio (TR), stripping agent, and carrier concentration. However, certain parameters such as homogenizer speed, emulsification time, surfactant concentration, extraction time, and pH of the simulated feed solution were kept constant in this study. The most favourable parameters for achieving maximum copper extraction and recovery were determined such as TR of 1:3, agitation speed (250 rpm), LIX 84 (0.2 M) in kerosene as the carrier, and H2SO4 (0.5 M) as the stripping agent. Using these conditions, approximately 74% of the copper was extracted while 37% was recovered with an acceptable ELM stability indicated by a 20% membrane swelling. This research demonstrates the significant potential of the ELM process for extracting copper from wastewater generated by various industries.
Keywords: Emulsion liquid membrane, liquid waste, metal recovery, copper, LIX 84